NATURE-USE AND SUSTAINABLE DEVELOPMENT - V. A. Gorbanyov (Vestnik MGIMO-Universiteta)
The fundamental difference between a traditional economy and geoecological economy is discussed in the article. The deeper the economy is being introduced into the ecosystem, the stronger it will be pressure on it that is outside the ecosystem, the more destructive is this incompatibility. It is concluded that the geoecological sustainable economy requires that the laws of geoecology became the basis of economic policy. Rational nature-use is impossible without an understanding of the unity of society and nature, their historical development of mutual. Our challenge is to create a new economy, acting on geoecological laws, this task is quite feasible, but if we can make the market called the true price of goods and services, that is taking into account the ecosystem services. The article shows that humanity is now faced with two interrelated problems: First - this is a problem of rational use of geoecosystem services, including natural resources, and secondly - the problem of environmental protection of pollution and save geoecosystem services, that is there are two "sides of the coin" - geoecological and resource. The relationship of the concept of rational nature-use, developed by Soviet scientists in the mid-twentieth century, and the concept of sustainable development, suggested by Western scientists is studied. It is shown that sustainable development - this is more a slogan than a scientific concept, which is unlikely to be implemented at the local level. At the same time, the concept of rational nature-use is feasible in regions or individual countries. At the same time, it is concluded that there is no sense to abandon the idea of sustainable development, as it is in itself a very humane, has received wide international recognition, does not carry negative consequences, but you should always keep in mind that essentially - we are not talking about sustainable development but about rational nature-use in a given area of the globe. The examples of indicators of sustainable development are given in the article.